Mineral and Rock Characteristics Identification Training Program for Geology-Mining Students at SMK Negeri 5 Barru - Andi Febby Alvionita; Sufriadin .; Purwanto .; Rini Novrianti Sutardjo Tui; Asta Arjunoarwan Hatta; Irzal Nur; Muhammad Ramli; Aryanti Virtanti Anas; Sri Widodo; Rizki Amalia; Andi Abdi Ibnurus; Muhammad Nur Halis (Faculty of Engineering UNHAS, 2026)
An understanding of mineral and rock science is a fundamental competency that is critically important for prospective workers in the mining sector, particularly in geology and exploration. However, the main challenge faced by vocational schools is the limited availability of laboratory facilities and learning methods that are still predominantly theory-oriented, resulting in very limited opportunities for students to conduct practical hands-on activities. This condition has the potential to hinder students’ mastery of practical skills in the long term. In response to this issue, lecturers and students from the Department of Mining Engineering at Hasanuddin University carried out a training program that included the delivery of basic material, tutorials on rock description, and mineral identification using 18 rock samples consisting of igneous, sedimentary, and metamorphic rocks. This community service activity was designed to enhance the conceptual understanding and practical skills of 25 students from the Mining Geology Department at SMK Negeri 5 Barru. The effectiveness of the training was evaluated through pre- and post-tests, which indicated an increase in the average score from 52 to 72 on a 100-point scale. As a follow-up, rock samples were handed over to the school to support sustainable learning. This training was proven to improve students’ readiness and practical competence as an important preparation for entering the workforce in the field of mining geology.